Long-term species richness-abundance dynamics in relation to species departures and arrivals in wintering urban bird assemblages - Suhonen J.; Jokimäki J. (Sciendo, 2022)
Temporal dynamics of local assemblages depend on the species richness and the total abundance of individuals as well as local departure and arrival rates of species. We used urban bird survey data collected from the same 31 study plots and methods during three winters (1991–1992; 1999–2000 and 2009–2010) to analyze the temporal relationship between bird species richness and total number of individuals (abundance). We also evaluated local departures and arrivals of species in each assemblage. In total, 13,812 individuals of 35 species were detected. The temporal variation in bird species richness followed the variation in the total number of individuals. The numbers of local departure and arrival events were similar. Also, the mean number of individuals of the recently arrived species (8.6) was almost the same as the mean number of individuals of the departed species (8.2). Risk of species departure was inversely related to number of individuals. Local species richness increased by one species when the total abundance of individuals increased by around 125 individuals and vice versa. Our results highlight the important role of local population departures and arrivals in determining the local species richness-abundance dynamics in human-dominated landscapes. Local species richness patterns depend on the total number of individuals as well as both the departure-arrival dynamics of individual species as well as the dynamics of all the species together. Our results support the more individuals hypothesis, which suggests that individual-rich assemblages have more species.